Pendampingan Revitalisasi Pendapatan melalui Sabun Kunyit, Solusi Inovatif Kesinambungan Pendapatan Ibu Rumah Tangga - Meliza, Juli; Zuhri, Zuhri; Winata, Edi; Ariesa, Yeni; Krisna Marpaung, Fenny (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower housewives through the production and sale of natural turmeric-based soap, which has the potential to increase family income. The activity method consists of several stages, including participant recruitment, training in turmeric soap making, and product marketing guidance. Data used included a survey of initial income, soap production levels, and additional income after sales. The results of the activity showed that participants were able to produce good quality soap and earn significant additional income. This activity had a positive impact on the household economy of participants, with an average increase in income of 30%. In addition, this activity also raised awareness of the importance of using natural, environmentally friendly products. These findings support the importance of empowering housewives through innovative products based on natural ingredients, which can serve as a model for economic empowerment programs in other regions